The steady state pharmacokinetics of trientine in Wilson disease patients - Pfeiffenberger, Jan; Weiss, Karl Heinz (European journal of clinical pharmacology, 2018)
To determine the steady state pharmacokinetics of trientine in children (≥ 12 years of age) and adult patients who had been receiving trientine dihydrochloride therapy prior to the study. Twenty patients were exposed to trientine (trientine dihydrochloride capsules supplied by Univar) after standard oral dosing as part of ongoing therapy. Plasma trientine concentration was determined pre-dose and at 30 min, 1, 1.5, 2, 3, 4, 5, 6, 8, and 12 h post-dose. Concentrations of trientine in plasma were determined by LC-MS/MS using a validated bioanalytical method with stable labelled trientine as the internal standard. Trientine was generally absorbed fairly rapidly with a median Tmax of 1.49 h (range, 0.48-4.08 h). There was some variability in exposure, with a 10-fold range in Cmax, and a 13.8-fold range in AUC0-t. This variability was slightly lower when PK parameters were dose-normalised (6.7-fold range in Cmax/D and an 11.6-fold range in AUC0-t/D). The terminal half-life, which could be defined in 14 of the 20 patients, was broadly consistent between patients (range of 2.33 to 6.99 h). There was no marked difference in pharmacokinetics between adult patients (n = 16) and children (n = 4). The Cmax range was 506 to 3100 ng/mL in adults and 309 to 1940 ng/mL in children—the equivalent ranges for AUC0-t were 1240 to 17,100 ng/mL h and 1500 to 8060 ng/mL h. When PK parameters were normalised for administered dose, the Cmax/D and AUC0-t/D for children were contained within the ranges for the adult patients. The steady state pharmacokinetics of trientine in Wilson disease patients were broadly similar to that reported in healthy subjects.